The Fate of a Crown - Baum, L. Frank (Saga Egmont, 2021)
First published under the pseudonym Schuyler Staunton, ‘The Fate of a Crown’ is one of L. Frank Baum’s early adventure stories aimed at an adult audience. Set in the revolutionary Brazil of 1889, young Robert Harcliffe takes up a job in Brazil as secretary for wealthy politician Dom Miguel de Pintra. Leader of the revolutionaries, Dom Miguel is plotting to overthrow the monarchy of Dom Pedro, and Harcliffe soon realises that is has entered into a dangerous world.